An Ar-rahnu Shop Acceptance Model (ARSAM) - Hanudin Amin; Chong, Rosita Katherine @ Rosidawati; Hazmi Dahlan; Rostinah Supinah (Labuan Faculty of International Finance, Universiti Malaysia Sabah, 2007)
The objective of this study is to examine the factors affect the local people of Labuan to accept ar-Rahnu shop (Islamic-based pawnshop). Considering this objective, the current study tends to develop a model, a theoretical framework to explain the factors influencing consumers’ acceptance of Islamic-based pawnshop. The model was tested with a survey sample (N = 384). The model labeled as an ARSAM (ar-Rahnu Shop Acceptance Model). Findings are useful for the local authorities or businesses to take initiative to develop an ar-Rahnu shop in order to promote Islamic-based economy among women as well as men minority. It is also treated as an eye-opener about the importance of having that system in Labuan. Totally, the study renders an overview of the ar-Rahnu shop acceptance among the Labuan local people, thus creating a chance to suggest a policy either to introduce an ar-Rahnu shop or to make the existing conventional pawnshops introduce window for ar-Rahnu.